Self-repairing ionizing hydrogel for wireless charging as well as preparation method and application of self-repairing ionizing hydrogel

By collecting and converting ultrasonic energy using self-healing ionization hydrogel, the limitations of existing energy collection conversion materials in wireless charging are solved, efficient and stable wireless charging is achieved, and the application range is expanded.

CN119391116APending Publication Date: 2025-02-07DONGHUA UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411520075.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing energy-collective conversion materials such as triboelectric generators and piezoelectric generators have problems with humidity influence, complex structure, low conversion efficiency and stability, and the driving energy is limited, making it difficult to achieve high-power wireless charging.

Method used

Self-healing ionized hydrogel is used to achieve wireless charging through ultrasonic energy collection and conversion. The hydrogel consists of hydrophilic polymers, conductive functional materials and calcium carbonate to form a dynamic physical entanglement network, with good mechanical adaptability and self-healing properties.

Benefits of technology

It realizes wireless charging in different scenarios, has high voltage electrical energy output, can work continuously and is not affected by high power ultrasound, expanding the application range of hydrogel materials in wireless charging and biological related fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391116A_ABST
    Figure CN119391116A_ABST
Patent Text Reader

Abstract

The invention relates to a self-repairing ionizing hydrogel for wireless charging and a preparation method and application thereof.The ionizing hydrogel is prepared from, by weight, 40-90 parts of hydrophilic polymer, 1-20 parts of conductive functional material, 10-20 parts of calcium carbonate and 2000-4000 parts of solvent. Controllable ultrasonic energy can be used as driving energy, and the self-repairing ionizing hydrogel can be applied to wireless charging. The ionizing hydrogel realizes wireless charging in different scenes through collection and conversion of ultrasonic energy. Compared with the prior art, the preparation process is simple, and the prepared ionizing hydrogel has good plasticity and self-repairing performance and has an excellent energy collection and conversion function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of wireless charging of hydrogels, and in particular to a self-repairing ionized hydrogel for wireless charging, and a preparation method and application thereof. Background Art

[0002] The current mainstream energy harvesting and conversion materials, such as triboelectric generators and piezoelectric generators, have some limitations. Triboelectric generators are easily affected by humidity and have a complex multi-layer structure, which increases manufacturing costs and maintenance difficulties; piezoelectric generators have low conversion efficiency and are difficult to generate high-power electrical energy; and these generators may be damaged under the action of high-intensity mechanical energy for a long time, affecting stability and reliability. In addition, the energy used to drive the generator also has limitations. For example, the energy of human movement is low, and the use of wind energy and tidal energy requires specific environmental conditions, which limits the application scenarios of the engine.

[0003] Conductive hydrogel is a material that can sense external stimuli and convert them into electrical signals. In addition to its application in the field of sensors, conductive hydrogel has also attracted attention for its energy collection and conversion capabilities. This material can collect energy from human movement, wind energy, ocean energy, vibration energy, etc. and convert it into electrical energy, which helps promote the development of green energy and alleviate the oil crisis. Due to its high flexibility and simple manufacturing process, conductive hydrogel shows broad application prospects in fields such as wearable charging devices and passive sensing systems.

[0004] Therefore, researching and developing new conductive hydrogels with energy harvesting and conversion functions is of great significance for improving energy utilization efficiency and expanding the scope of application. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a self-healing ionized hydrogel for wireless charging and its preparation method and application, so as to provide an effective solution for expanding the application scope of hydrogel materials in wireless charging and biological related fields.

[0006] During the process of conception, the applicant believed that the present invention utilizes controllable ultrasonic energy as a driving energy source, and the self-healing ionized hydrogel can be directly used as a generator by collecting and converting ultrasonic energy to achieve wireless charging in different scenarios.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] In one aspect, the present invention provides a self-repairing ionized hydrogel for wireless charging, comprising the following components in parts by weight:

[0009] Hydrophilic polymer 40-90 parts

[0010] 1 to 20 parts of conductive functional material

[0011] Calcium carbonate 10-20 parts

[0012] Solvent 2000~4000 parts

[0013] Furthermore, the hydrophilic polymer is any one of polyacrylic acid (PAA), polyacrylamide (PAM), polyvinyl alcohol (PVA), polyethylene glycol (PEG), and polyethylene oxide (PEO).

[0014] Preferably, the hydrophilic polymer is PAA.

[0015] Furthermore, the molecular weight of the hydrophilic polymer is 1000-10000000.

[0016] Furthermore, the conductive functional material is any one of metal nanoparticles / nanowires, liquid metal, carbon black, graphene, carbon nanotubes, transition metal carbonitride (MXene), conductive polymer, and polyelectrolyte.

[0017] Preferably, the conductive functional material is MXene.

[0018] Furthermore, the calcium carbonate is synthesized from sodium carbonate and calcium chloride.

[0019] Preferably, the mass ratio of sodium carbonate to calcium chloride is 1:(2-3).

[0020] Furthermore, the solvent is water.

[0021] On the other hand, the present invention provides a method for preparing the self-repairing ionized hydrogel for wireless charging as described above, wherein a calcium chloride solution, a hydrophilic polymer and a conductive functional material are stirred and mixed evenly, and then a sodium carbonate solution is added dropwise into the above-mentioned mixed solution to obtain the ionized hydrogel.

[0022] Preferably, the calcium chloride solution, the hydrophilic polymer and the conductive functional material are stirred for 15 to 60 minutes.

[0023] On the other hand, the present invention provides an application of the self-healing ionized hydrogel for wireless charging as described above, wherein the ionized hydrogel can collect ultrasonic energy and convert the ultrasonic energy into electrical energy to achieve subsequent wireless charging of electronic units.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) The hydrophilic polymer used in the present invention is a soft, ductile and self-repairable hydrogel matrix. The conductive functional material further improves the mechanical properties and conductive properties of the hydrogel. The hydrophilic polymer and the conductive functional material undergo supramolecular synergy to form a dynamic physical entanglement network. The network gives the hydrogel good mechanical adaptability, making the ionized hydrogel have good plasticity. When the network is broken by external force, the supramolecular synergy can promote the diffusion of polymer segments on the broken interface and re-entangle with the conductive functional material or other polymer segments, thereby forming a new and complete physical cross-linking network, so that the hydrogel has good self-repairing properties. Even under the action of high-power ultrasound, its structure will not be destroyed and high-voltage electrical energy can be continuously output.

[0026] (2) Compared with traditional energy collection and conversion devices, the preparation process of the ionizing hydrogel material provided by the present invention is simple. In terms of energy collection and conversion applications, the operation is simple and does not require complex device design. It can achieve wireless charging in different scenarios and has great potential in the application of implantable devices. It has a great driving effect on the construction of the Internet of Things network. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a test diagram of the plasticity and self-healing performance of the ionized hydrogel prepared in Example 1 of the present invention;

[0028] Figure 2 This is a graph showing the output power variation of the ionized hydrogel prepared in Example 1 of the present invention at different resistances;

[0029] Figure 3 This is a test diagram of the electrical properties of the ionized hydrogel prepared in Example 1 of the present invention;

[0030] Figure 4 The voltage diagram of the ionized hydrogel prepared in Example 1 under different media is shown in the present invention;

[0031] Figure 5 This is a voltage diagram of the present invention generated by ultrasound on the ionized hydrogel prepared in Example 1 at different pork thicknesses;

[0032] Figure 6 The present invention is a circuit diagram for converting output electricity using a rectifier;

[0033] Figure 7 This is a diagram of charging different capacitors after the ionized hydrogel prepared in Example 1 of the present invention converts ultrasonic energy into electrical energy. DETAILED DESCRIPTION

[0034] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. Any features such as preparation means, materials, structures or composition ratios not clearly described in this technical solution are regarded as common technical features disclosed in the prior art.

[0035] In the following embodiments: MAX (Ti3AlC2) raw material was purchased from Yiyi Technology Co., Ltd.; PAA was purchased from Shanghai McLean Biotechnology Co., Ltd., with an average molecular weight of 250,000; calcium chloride was purchased from Shanghai Titan Technology Co., Ltd.; sodium carbonate was purchased from Shanghai Lingfeng Chemical Reagent Co., Ltd.; lithium fluoride was purchased from Shanghai Aladdin Chemical Co., Ltd.; and hydrochloric acid solution was purchased from Sinopharm Group.

[0036] Preparation of MXene nanosheets: Weigh 1.5 g LiF powder and 40 mL concentrated hydrochloric acid, mix and stir for 30 minutes to dissolve the LiF powder and prepare an etching solution; weigh 2 g MAX (Ti3AlC2) raw material, slowly add the etching solution in batches, stir at 35°C for 24 hours to etch the MAX phase; repeatedly centrifuge and wash the above-mentioned etching products to remove the by-products of the etching reaction and dilute the acid solution, and finally freeze-dry to obtain MXene nanosheets.

[0037] Preparation of MXene / PAA / ACC hydrogel: 0.666 g of calcium chloride and 30 mL of water were prepared into a calcium chloride solution, and 0.318 g of sodium carbonate and 30 mL of water were prepared into a sodium carbonate solution. The calcium chloride solution, PAA and MXene nanosheets were stirred and mixed evenly, and then the sodium carbonate solution was added dropwise to the above mixed solution to obtain the MXene / PAA / ACC hydrogel.

[0038] Example 1

[0039] The present invention provides a method for preparing a self-healing ionized hydrogel for wireless charging, comprising stirring a calcium chloride solution, 1.23 g of PAA and 0.13 g of MXene nanosheets for 30 minutes to mix evenly, and then adding a sodium carbonate solution dropwise into the mixed solution to obtain a MXene / PAA / ACC hydrogel.

[0040] Example 2

[0041] The present invention provides a method for preparing a self-healing ionized hydrogel for wireless charging, comprising stirring a calcium chloride solution, 1.23 g of PAA and 0.09 g of MXene nanosheets for 30 minutes to mix evenly, and then adding a sodium carbonate solution dropwise into the mixed solution to obtain a MXene / PAA / ACC hydrogel.

[0042] Example 3

[0043] The present invention provides a method for preparing a self-healing ionized hydrogel for wireless charging, comprising stirring a calcium chloride solution, 1.23 g of PAA and 0.03 g of MXene nanosheets for 30 minutes to mix evenly, and then adding a sodium carbonate solution dropwise into the mixed solution to obtain a MXene / PAA / ACC hydrogel.

[0044] Comparative Example 1

[0045] The present invention provides a method for preparing a self-repairing ionized hydrogel for wireless charging. A calcium chloride solution and 1.23 g of PAA are stirred and mixed evenly, and then a sodium carbonate solution is added dropwise into the mixed solution to obtain a PAA / ACC hydrogel.

[0046] Table 1 MXene / PAA / ACC hydrogels with different ratios

[0047]

[0048] Test Example 1

[0049] Plasticity and self-healing properties of hydrogels:

[0050] See also Figure 1 The MXene / PAA / ACC hydrogel prepared in Example 1 can be molded into the shape of a flower. After a hydrogel flower is manually cut into four pieces and then re-glued, it can quickly return to its original shape, proving the rapid healing performance of the hydrogel.

[0051] The rheological test of MXene / PAA / ACC hydrogel prepared in Example 1 was carried out using a Hake Mars rotational rheometer. In the continuous step strain test, the amplitude alternated between 0.1% and 10%, which means that the sample will experience a process from very small deformation to larger deformation and then back to small deformation. G' (storage modulus) and G" (loss modulus) can be quickly restored to more than 90%, indicating that the cross-linked network of MXene / PAA / ACC hydrogel is constantly destroyed and reshaped, showing excellent self-healing properties.

[0052] Test Example 2

[0053] Electrical properties test of hydrogel:

[0054] The conductivity of the hydrogel was calculated by testing the electrochemical impedance spectroscopy (EIS) of the sample using an electrochemical workstation (Chenhua). Two stainless steel sheets were used as test electrodes, and the MXene / PAA / ACC hydrogel prepared in Example 1 was sandwiched between the two stainless steel sheets. The cross-sectional area (S) of the hydrogel was 1.89 cm 2, thickness (l) is 0.1cm, the calculation formula of ionic conductivity (σ) is: σ=l / RS, where R is resistance; the calculation formula of output power (P) is: P=UI, where U is open circuit voltage and I is short circuit current.

[0055] As can be seen from Table 2, the conductivity of MXene / PAA / ACC hydrogel is as high as 2S m -1 , while the conductivity of PAA / ACC hydrogel without MXene nanosheets is only 0.2 S m -1 , and the conductivity of MXene / PAA / ACC hydrogel increases with the increase of MXene nanosheets content. In addition, the output voltage also increases with the increase of MXene nanosheets.

[0056] Table 2 Electrical properties test of MXene / PAA / ACC hydrogel

[0057]

[0058] See also Figure 2 and Figure 3 Under 22kHz, 6.5W ultrasound, an oscilloscope (MDO3024, Tektronix) was used for voltage testing, and a multimeter (DAQ6510, Geely, USA) was used for current testing. The MXene / PAA / ACC hydrogel prepared in Example 1 can generate an open circuit voltage of 85V, and the output voltage of the hydrogel increases with the increase of the external resistance; at a short-circuit current of 1.5μA, the output voltage of the hydrogel decreases with the increase of the external resistance; when the external resistance is 0.01MΩ, it has a maximum output power of 85μW.

[0059] See also Figure 4 , under different media, the MXene / PAA / ACC hydrogel material prepared in Example 1 was subjected to ultrasonic stimulation at 22kHz and 6.5W, with different voltage outputs. The water medium was 26.5V, the coupling agent medium was 58.4V, the PAM hydrogel medium was 61.2V, and the pork medium was 69.4V, which proved the energy collection and conversion ability of the hydrogel material, and can be used for wireless charging of other electronic units in different scenarios.

[0060] See also Figure 5 For pork media of different thicknesses, the voltage drop is not obvious. Even under the isolation of 8 cm pork media, there is still a voltage output of 61.4 V, which proves that the ionized hydrogel material that can be used for energy collection and conversion has a good application prospect in human implantable devices and biosensors.

[0061] See also Figure 6 and Figure 7In order to verify the potential of ionized hydrogel materials that can be used for energy collection and conversion in wireless charging, and can effectively convert ultrasonic energy into high-output electrical energy, and store and utilize it, a circuit diagram was designed. After the ionized hydrogel prepared in Example 1 was subjected to ultrasonic stimulation at 22kHz and 6.5W, the generated alternating current was rectified to obtain direct current, and the electrical energy was stored in the capacitor. Before rectification, the MXene / PAA / ACC hydrogel can directly generate an AC voltage of 85V, and after rectification, it can reach a DC voltage of 120V. After converting ultrasonic energy into electrical energy, the MXene / PAA / ACC hydrogel can quickly charge the capacitor. When charging a 10μF capacitor, the ultrasonically driven MXene / PAA / ACC hydrogel can charge it to 83V within 20 seconds; for capacitors with a capacity of 22μF and 47μF, the voltages after charging for 20 seconds are 57V and 31V, respectively.

[0062] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A self-repairing ionized hydrogel for wireless charging, characterized in that: The composition comprises the following components by weight: Hydrophilic polymer 40-90 parts 1 to 20 parts of conductive functional material Calcium carbonate 10-20 parts 2000-4000 parts of solvent.

2. The self-repairing ionized hydrogel for wireless charging according to claim 1, characterized in that: The hydrophilic polymer is any one of polyacrylic acid, polyacrylamide, polyvinyl alcohol, polyethylene glycol, and polyethylene oxide.

3. The self-repairing ionized hydrogel for wireless charging according to claim 1, characterized in that: The molecular weight of the hydrophilic polymer is 1000-10000000.

4. The self-repairing ionized hydrogel for wireless charging according to claim 1, characterized in that: The conductive functional material is any one of metal nanoparticles / nanowires, liquid metal, carbon black, graphene, carbon nanotubes, transition metal carbonitrides, conductive polymers, and polyelectrolytes.

5. The self-repairing ionized hydrogel for wireless charging according to claim 1, characterized in that: The calcium carbonate is synthesized from sodium carbonate and calcium chloride.

6. The self-repairing ionized hydrogel for wireless charging according to claim 1, characterized in that: The mass ratio of the sodium carbonate to calcium chloride is 1:(2-3).

7. The self-repairing ionized hydrogel for wireless charging according to claim 1, characterized in that: The solvent is water.

8. A method for preparing a self-repairing ionized hydrogel for wireless charging according to any one of claims 1 to 7, characterized in that: The calcium chloride solution, the hydrophilic polymer and the conductive functional material are stirred and mixed evenly, and then the sodium carbonate solution is added dropwise into the mixed solution to obtain the ionizing hydrogel.

9. The method for preparing a self-repairing ionized hydrogel for wireless charging according to claim 8, characterized in that: The calcium chloride solution, the hydrophilic polymer and the conductive functional material are stirred for 15 to 60 minutes.

10. An application of a self-repairing ionized hydrogel for wireless charging as claimed in any one of claims 1 to 7, characterized in that: The ionized hydrogel can collect ultrasonic energy and convert the ultrasonic energy into electrical energy, thereby realizing wireless charging of subsequent electronic units.

Citation Information

Patent Citations

  • Anti-freezing self-repairing conductive hydrogel and preparation method thereof and flexible sensor

    CN112608508A

  • Polyvinyl alcohol-sodium alginate conductive hydrogel microbead as well as preparation and application thereof

    CN117106206A

  • Self-repairing conductive hydrogel based on modified MXene as well as preparation method and application of self-repairing conductive hydrogel

    CN118755148A